Efficient transient photocurrent generation in waveguide-type bacteriorhodopsin photocells. (17th January 2018) - Yamada, Toshiki; Kasai, Katsuyuki; Kaji, Takahiro; Tominari, Yukihiro; Tanaka, Shukichi; Otomo, Akira
Abstract: A new waveguide-type bacteriorhodopsin (bR) photocell was produced by modifying the structure of a conventional bR photocell. We investigated the transient photo-current characteristics of the waveguide-type bR photocell, and compared them with those of the conventional bR photocell at the vertical incidence. Largely efficient photocurrent generation from the waveguide-type bR photocell was observed by the efficient coupling of the light-matter interaction, compared with that of the conventional bR photocell at the vertical incidence. The incident angle and polarization dependences for the excitation light were also investigated for the waveguide-type bR photocells. Waveguide structures are very useful in preparing efficient bR photo-sensor devices and sensing devices using bR thin films.